2013
DOI: 10.1089/aid.2012.0322
|View full text |Cite
|
Sign up to set email alerts
|

Feline Glycoprotein A Repetitions Predominant Anchors Transforming Growth Factor Beta on the Surface of Activated CD4+CD25+Regulatory T Cells and Mediates AIDS Lentivirus-Induced T Cell Immunodeficiency

Abstract: Using the feline immunodeficiency virus (FIV) model for AIDS-lentivirus infection, our laboratory has previously demonstrated that T regulatory (Treg) cell-mediated immune T and B cell dysfunction contributes to lentivirus persistence and chronic disease through membrane bound transforming growth factor beta (mTGFb). Studying Treg cells in the context of infection has been problematic as no inducible marker for activated Treg cells had been identified. However, recent reports in human Treg studies have describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…Studies have reported that TGF-␤ is expressed on the surface of activated Treg cells and plays a role in contact-dependent Tregmediated suppression (3,15,17,18). Furthermore, we have demonstrated that GARP forms a complex with membrane-bound TGF-␤ (mTGF-␤) on activated Treg cells (18).…”
Section: Fig 4 Fiv-infected Treg Cells Suppress Cd4mentioning
confidence: 72%
See 4 more Smart Citations
“…Studies have reported that TGF-␤ is expressed on the surface of activated Treg cells and plays a role in contact-dependent Tregmediated suppression (3,15,17,18). Furthermore, we have demonstrated that GARP forms a complex with membrane-bound TGF-␤ (mTGF-␤) on activated Treg cells (18).…”
Section: Fig 4 Fiv-infected Treg Cells Suppress Cd4mentioning
confidence: 72%
“…Furthermore, we have demonstrated that GARP forms a complex with membrane-bound TGF-␤ (mTGF-␤) on activated Treg cells (18). As FIV infection induced GARP expression on CD4…”
Section: Fig 4 Fiv-infected Treg Cells Suppress Cd4mentioning
confidence: 93%
See 3 more Smart Citations